Integration of Merdeka Curriculum with Zero Waste Movement: an Innovative Key in Solving Environmental Damage - Herman, Maman; Nur, Mulyana (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2024)
Based on previous research, environmental damage caused by waste is due to people's habit of littering. One of the solutions that can be taken is by integrating the Independent Curriculum with the Zero Waste Movement. This study aims to explore the integration of the Zero Waste Movement in the Merdeka Curriculum, with a focus on intra-curricular activities, extracurricular activities, school culture, and strengthening projects for Pancasila Student Profiles. This study uses a literature study approach, by reviewing various relevant sources and analyzing how such integration can be carried out effectively. The results of the study show that integration with the Merdeka Curriculum covers certain subjects that support the understanding and practice of Zero Waste. In extracurricular activities, the Zero Waste Movement can be made a work program by members (Adiwiyata cadres). The Zero Waste Movement can become a school culture if all school members actively participate in the 5R activities (Reduce, Reuse, Recycle, Refuse, and Rot) repeatedly, scheduled, organized, and can be evaluated. The Zero Waste Movement is part of the project to strengthen the Pancasila Student Profile, with schools holding co-curricular activities in the form of student projects that support the implementation of the movement. In conclusion, the integration of the Zero Waste Movement into the Merdeka Curriculum not only has the potential to increase environmental awareness among students but also to strengthen Pancasila values, making it an integral part of character education and school culture.